LAJU PERTUMBUHAN DAN KELANGSUNGAN HIDUP LARVA IKAN BETOK (Anabas testudineus) PADA BERBAGAI PERIODE PERGANTIAN JENIS PAKAN - RIRI MARIANA SARI; YULISMAN .; MUSLIM . (Universitas Sriwijaya, 2015)
ABSTRACT The aims of this research were to determining the right changed periode of Artemia sp., Moina sp., and artificial feed as fed of climbing perch (Anabas testudineus) larvae to growth and survival rate.The research used completely randomized design with three treatments and three replications. The treatment was difference changed periode of Artemia sp., Moina sp., and artificial feed as fed of climbing perch (Anabas testudineus) larvae. Artemia sp. were fed at 3–15 days after hatching, Moina sp. were fed at 14 – 24 days after hatching and artificial feed at 21–33 days after hatching (I: 3-15, II: 14-24, III: 21-33) as treatment A; Artemia sp. were fed at 3–11 days after hatching, Moina sp. were fed at 10 – 20 days after hatching, and artificial feed at 17–33 days after hatching (I: 3-11, II: 10-20, III:17-33) as treatment B; Artemia sp. were fed at 3–7 days after hatching, Moina sp. were fed at 6-18 days after hatching and artificial feed at 15–33 days after heatching ( I: 3-7, II: 6-18, III: 15-33) as treatment C. Fish were fed three times a day at 8 am, 10.30 am, 1 pm, 3.30 pm, 6 pm using at satiation method.Based on Analysis of Variance (ANOVA), the results showed significant difference effect in specific weight growth rate but no significant difference effect in specific lenght growth rate. Result of Honestly Significance Difference test showed the highest specific weight growth rate was treatment C, but no significant difference with treatment B. The best treatment for survival rate was treatment A which significant difference with treatment C but no significant difference with treatment B. As long as research, water quality was in optimum range for climbing perch (Anabas testudineus) larvae rearing. Temperature was 27-28 oC , DO 3.38-5.06 mg.L-1 , pH 4.4-6.6, ammonia 0.002-0.008 mg.L-1. Keywords:Climbing perch, feed type, feed changing period, survival rate, growth rate